Pengaruh Model Project Based Learning Terhadap Tingkat Kolaboratif Siswa dalam Pembelajaran Pendidikan Pancasila (Studi Kuasi Eksperimen di Kelas XI MA Negeri 1 Kota Bandung): Penelitian - Tina Sari Mareta; Endang Danial; Dede Iswandi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to investigate the effect of the Project Based Learning (PjBL) model on students’ collaborative skills in Pancasila Education. The background of this research is based on the importance of mastering 21st-century skills, particularly collaboration, as a crucial aspect of current educational demands. The study employs a quantitative approach with a quasi-experimental design, involving two classes: an experimental class applying the Project Based Learning model and a control class using conventional teaching methods. Data were collected through essay-based tests to measure students’ collaborative skills and were analyzed using a t-test. The findings show a significant difference in posttest results between the experimental and control classes. The experimental class demonstrated a higher improvement in collaborative skills. The Project Based Learning model is considered more effective as it allows students to actively engage in teamwork, group discussions, and joint decision-making. In contrast, conventional teacher-centered learning tends to limit student interaction, which hinders the development of collaboration. Therefore, the Project Based Learning model is recommended as an alternative instructional strategy to enhance students’ collaborative skills in Pancasila Education.